A review on intelligent process for smart home applications based on IoT: coherent taxonomy, motivation, open challenges, and recommendations - Zaidan, A. A. (Tanjong Malim, 2020)
A review on intelligent process for smart home applications based on IoT: coherent taxonomy, motivation, open challenges, and recommendations by Zaidan, A. A.